Tattoo: Attitudes and Perception of Health-related Risks - Refaie Yaseen Hammed Al-Hussein (Kufa Journal for Nursing Sciences)
Background: For thousands of years, and in many places around the world tattoos have been practiced, while it comes into existence spontaneously and practiced in cultural, geographic and climatic conditions completely.